The quantitative characteristic of morphological and structural changes in the diverted regions of the large intestine - A. S. Akopyan; E. V. Manukyan; T. G. Bagdasaryan; A. F. Abramyan; A. A. Akopyan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
Aim of investigation. Radical surgery at complicated forms of colorectal cancer frequently results in colostoma formation. In due course in diverted regions colitis of non-infectious character educes. The study is devoted to revealing of degree of morphological changes of defunctioning loop wall in relation to terms of colostoma formation.Material and methods. Tissues received at resection of nonfunctioning regions of intestinal stump in 255 patients were subject of the study. Morphological investigation was carried out under the practical standard with staining of samples by hematoxylin and eosine. Stereometric analysis principles were used. Reconstructive and restitutional operations with formation of transverse-rectal or sigmoido-rectal anastomoses «end-to-end» with liquidation of colostoma in various terms, but mostly in 2–2,5 months (early surgical rehabilitation).Results. Investigations demonstrated development of processes of remodeling in mucosa of defunctioning loop of atrophic type with decrease of quantity of mucus-producing epithelial cells. Simultaneously on a background of developing immunodeficiency there was progression of inflammatory processes, up to microabscess development. The direct interrelation between degree of «diversive» colitis and terms of intestine diversion from intestinal passage was is found. At early surgical rehabilitation in 125 patients no incompetence of anastomosis was observed. The postoperative morbidity rate was 7,2 % (9 patients).Conclusions. Moderate inflammatory changes in defunctioning loop do not influence processes of healing of interintestinal anastomosis at early surgical rehabilitation.